2001
DOI: 10.1017/s1357729800055788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental levels of chromium picolinate on the growth performance, serum traits, carcass characteristics and lipid metabolism of growing-finishing pigs

Abstract: This study investigated the effect of chromium picolinate supplementation on growth performance, carcass characteristics and lipid metabolism of growing-finishing pigs. Sixty Landrace ✕ Yorkshire ✕ Duroc (LYD) pigs with a mean initial body weight of 46·65 (s.e. 6·72) kg were randomly allocated into three groups with two replicates. They were supplemented with 0 , 200, or 400 μg/kg (ppb) chromium in the organic form of chromium picolinate for 90 days. Supplementation with chromium picolinate in the pigs’ ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 40 publications
3
22
1
12
Order By: Relevance
“…Dietary fat has been reported to elevate blood insulin and glucose [48,49]. Supplemental Cr lowered circulating insulin concentration in rats fed HFD [12] and in swine [28]. In the present study, plasma insulin concentration of pigs fed HFD linearly decreased by Cr supplementation on d 14.…”
Section: Respiratory Ratesupporting
confidence: 52%
See 2 more Smart Citations
“…Dietary fat has been reported to elevate blood insulin and glucose [48,49]. Supplemental Cr lowered circulating insulin concentration in rats fed HFD [12] and in swine [28]. In the present study, plasma insulin concentration of pigs fed HFD linearly decreased by Cr supplementation on d 14.…”
Section: Respiratory Ratesupporting
confidence: 52%
“…Since Page et al [25] reported that the supplemental Cr increased LMA and percentage of muscling but decreased the tenth rib backfat, similar effects of supplemental Cr have been demonstrated [26,28]. In other studies, contrastingly, supplemental Cr was ineffective in modulating carcass leanness or fatness of pigs [29][30][31].…”
Section: Carcass Traitsmentioning
confidence: 73%
See 1 more Smart Citation
“…While the present results showed that graded levels of dietary chromium as CrMet have no significant effect on growth performance in either the individual period or total experimental period in pigs as body weights grow from 30 to 100 kg, as well as carcass traits, nevertheless, pigs fed 200 μg/kg chromium as CrMet had a numerically greater value in LMA than the control (P<0.10). A tendency to increase in LMA may be due to increased insulin activity by chromium which stimulates amino acid transport and protein synthesis in muscle cells [31], or increased secretions or mRNA levels of growth hormone and insulin like growth factor-I which accelerate protein anabolism [20,32,33]. Moreover, the present result of a numerical increase in the 10th rib fat in 200 μg/kg chromium groups (P<0.10) indicated that chromium addition may promote adipose lipogenesis, which was demonstrated by Lien et al [34] who found that long-term exposure to chromium picolinate (CrPic) in growing-finishing pigs increased the activities of adipose tissue lipogenesis related enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of dietary Cr on fasting glucose concentrations in pigs are inconsistent. Some studies reported that dietary Cr significantly reduces fasting glucose (Lien et al 2001;Wang et al 2001Wang et al , 2009b, whereas others reported no effect (Amoikon et al 1995;Matthews et al 2001). Amoikon et al (1995) reported that CrPic increased insulin sensitivity as assessed by increased glucose clearance rate and decreased glucose half-life during a glucose tolerance test and insulin challenge test in pigs.…”
Section: Discussionmentioning
confidence: 99%